Behavioural and psychological symptoms in general hospital patients with dementia, distress for nursing staff and complications in care: results of the General Hospital Study. (9th January 2017) - Hessler, J. B.; Schäufele, M.; Hendlmeier, I.; Junge, M. N.; Leonhardt, S.; Weber, J.; Bickel, H.
Abstract : Aims: Little is known about how behavioural and psychological symptoms of dementia (BPSD) manifest in the general hospital. The aim was to examine the frequency of BPSD in general hospitals and their associations with nursing staff distress and complications in care. Methods: Cross-sectional representative study with 1469 patients aged ≥65, including 270 patients with dementia, of 33 randomly selected general hospitals in Germany. BPSD and complications were reported by nurses. Results: Overall frequency of BPSD was higher in patients with dementia (76%) than without (38%). The most frequent symptoms in patients with dementia were nighttime disturbances (38%), depression (29%) and aberrant motor behaviour (28%) and the most distressing symptoms for nursing staff were delusions, aggression and nighttime disturbances. The overall frequency of BPSD increased from 67% in mild dementia, to 76% in moderate dementia and to 88% in severe dementia. The most frequent symptoms in patients without dementia were depression (19%), nighttime disturbances (13%) and irritability (13%). The most distressing symptoms were aggression and delusions, while the same symptoms were consistently rated as less distressing than in patients with dementia. Factor analysis revealed three independent groups of BPSD that explained 45% of the total variance. First, expansive symptoms (aggression, irritability, nighttime disturbances, aberrant motor behaviour and disinhibition) were frequent, distressing for nursing staff and associated with many complications. Second, psychotic symptoms (delusions and hallucinations) were infrequent, distressing and associated with some complications. Third, affective symptoms (apathy, anxiety and depression) were frequent, non-distressing and associated with few complications. The results did not change when cases with delirium were excluded from both groups. Conclusions: BPSD are common in older hospital patients with dementia and associated with considerable distress in nursing staff, as well as a wide range of special treatments needs and additional behavioural and medical complications. Management strategies are needed to improve the situation for both patients and hospital staff.